A Single 48 mg Sucralose Sip Unbalances Monocyte Subpopulations and Stimulates Insulin Secretion in Healthy Young Adults - Angélica Y. Gómez-Arauz; Nallely Bueno-Hernández; Leon F. Palomera; Raúl Alcántara-Suárez; Karen L. De León; Lucía A. Méndez-García; Miguel Carrero-Aguirre; Aaron N. Manjarrez-Reyna; Camilo P. Martínez-Reyes; Marcela Esquivel-Velázquez; Alejandra Ruiz-Barranco; Neyla Baltazar-López; et al. (Journal of Immunology Research)
Sucralose is a noncaloric artificial sweetener that is widely consumed worldwide and has been associated with alteration in glucose and insulin homeostasis. Unbalance in monocyte subpopulations expressing CD11c and CD206 hallmarks metabolic dysfunction but has not yet been studied in response to sucralose. Our goal was to examine the effect of a single sucralose sip on serum insulin and blood glucose and the percentages of classical, intermediate, and nonclassical monocytes in healthy young adults subjected to an oral glucose tolerance test (OGTT). This study was a randomized, placebo-controlled clinical trial. Volunteers randomly received 60 mL water as placebo (n=20) or 48 mg sucralose dissolved in 60 mL water (n=25), fifteen minutes prior to an OGTT. Blood samples were individually drawn every 15 minutes for 180 minutes for quantifying glucose and insulin concentrations. Monocyte subsets expressing CD11c and CD206 were measured at -15 and 180 minutes by flow cytometry. As compared to controls, volunteers receiving sucralose exhibited significant increases in serum insulin at 30, 45, and 180 minutes, whereas blood glucose values showed no significant differences. Sucralose consumption caused a significant 7% increase in classical monocytes and 63% decrease in nonclassical monocytes with respect to placebo controls. Pearson’s correlation models revealed a strong association of insulin with sucralose-induced monocyte subpopulation unbalance whereas glucose values did not show significant correlations. Sucralose ingestion decreased CD11c expression in all monocyte subsets and reduced CD206 expression in nonclassical monocytes suggesting that sucralose does not only unbalance monocyte subpopulations but also alter their expression pattern of cell surface molecules. This work demonstrates for the first time that a 48 mg sucralose sip increases serum insulin and unbalances monocyte subpopulations expressing CD11c and CD206 in noninsulin-resistant healthy young adults subjected to an OGTT. The apparently innocuous consumption of sucralose should be reexamined in light of these results.